Imprensa alternativa e contracultura: o jornal brasileiro Rolling Stone de 1972 - Ribas, Ana Helena Fabbro Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The present monograph is a historical research of one of the brazilian newspapers in a journalistic heterogeneous effervescence, referring to the proliferation of vehicles on alternative libertarians of the 60/70. The project gives visibility to the Rolling Stone newspaper as the document that disproved their own relevancy in the viability of the music production and counterculture inspired by North America, developing the repercussion of the new behavior of young flower power in the country. The personality of those who were in the journalistic team, the production schema, editorial and proposed tariffs would be in total congruency with the countercultural movement

O presente trabalho é uma pesquisa histórica de um dos jornais nacionais de um período de efervescência jornalística heterogênea, referente à proliferação de veículos libertários na imprensa alternativa da década de 60/70. O projeto dá visibilidade ao jornal Rolling Stone como documento que comprovaria sua própria relevância na viabilização da produção musical e (contra) cultural norte-americana como informação para o público brasileiro e pela repercussão do novo comportamento dos jovens do flower power no país. A personalidade dos que estavam na equipe jornalística, o esquema de produção, editorial e pautas propostas estariam em total congruência com o movimento contracultural
Keywords: Contracultura; Imprensa alternativa; Jornalismo; Counter culture